Analisis Kimiawi Darah: Kadar Glukosa dan Kolesterol pada Manusia serta pH Darah pada Unggas - Hera Aulia Brilian; Suci Rahmadani; Ahmad Yanuar Naufal Al-Fatan; Apriliyana Dewi; Zuhratul Amaliyyah Wietya Ulva; Agna Vika; Hilda Nurul Lintang; Sarah Melodia Azzahra; Arina Manasikal Khusna (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Blood is a major component of the homeostatic system that plays an essential role in maintaining the physiological balance of the body. Several blood chemistry parameters, including blood glucose, cholesterol, and blood pH levels, can be used to assess an individual's health condition. Blood glucose is derived from carbohydrate metabolism and serves as the body's primary energy source. Cholesterol is a lipid compound involved in cell membrane formation and hormone synthesis and consists of Low-Density Lipoprotein (LDL) and High-Density Lipoprotein (HDL). Blood pH measurement is used to determine the degree of acidity or alkalinity of the blood, reflecting the body's acid-base balance. This study aims to interpret the results of blood chemical analyses and understand the principles and methods used to determine blood glucose, cholesterol, and pH levels. The research employed a laboratory experimental method by measuring these parameters using blood chemistry testing equipment on blood samples. The results showed that fasting blood glucose was 97 mg/dL, indicating a normal glucose level. In contrast, non-fasting blood glucose was 61 mg/dL, which was below the normal range and indicated hypoglycemia. Blood cholesterol was measured at 139 mg/dL, which remained within the normal range. The blood pH value was 6, indicating a condition of acidosis. These findings highlight the importance of blood chemistry examinations as indicators for evaluating metabolic conditions and overall health status.